2016
DOI: 10.1155/2016/4372852
|View full text |Cite
|
Sign up to set email alerts
|

Xerostomia, Hyposalivation, and Salivary Flow in Diabetes Patients

Abstract: The presence of xerostomia and hyposalivation is frequent among diabetes mellitus (DM) patients. It is not clear if the presence of xerostomia and hyposalivation is greater in DM than non-DM patients. The aims of this systematic review are (1) to compare the prevalence rates of xerostomia, (2) to evaluate the salivary flow rate, and (3) to compare the prevalence rates of hyposalivation in DM versus non-DM population. This systematic review was conducted according to the PRISMA group guidelines by performing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
95
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 26 publications
(90 reference statements)
2
95
0
5
Order By: Relevance
“…The reduced availability of such a protective factor could be linked to the inadequate preservation of mouth tissues and the consequent high incidence of caries and oral infections reported in diabetic subjects. Other studies have shown altered protein concentrations and a decreased salivary flow in diabetic patients (L opez-Pintor et al, 2016). Melatonin itself seems to stimulate secretion by salivary glands, as revealed by melatonin-induced morphological changes in acinar cells of human parotid glands, which have been associated with exocytotic activity, and, ultimately, in protein secretion (Loy et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…The reduced availability of such a protective factor could be linked to the inadequate preservation of mouth tissues and the consequent high incidence of caries and oral infections reported in diabetic subjects. Other studies have shown altered protein concentrations and a decreased salivary flow in diabetic patients (L opez-Pintor et al, 2016). Melatonin itself seems to stimulate secretion by salivary glands, as revealed by melatonin-induced morphological changes in acinar cells of human parotid glands, which have been associated with exocytotic activity, and, ultimately, in protein secretion (Loy et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…So diabetes is one of the main causes for oral hygiene and destruction of the teeth. 7 Cortelli et al in their study evaluate the impact of gingivitis treatment on oral health and quality of life. This treatment can improve quality of life and emphasize the relevance of periodontal care for individual's daily life.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] The reduction of salivary gland secretion may also be caused by the occurrence of endocrinopathy (diabetes, thyroid disease), autoimmune diseases (Sjögren's syndrome, rheumatoid arthritis, systemic lupus erythematosus, scleroderma), granulomatous diseases, and local causes (head and neck radiotherapy, salivary gland diseases). 11,14,15 Xerostomia has certain effects on the emotional state of the elderly, leading to a low mood and depressive states. Both subjective and objective complaints associated with dry mouth reduce the quality of life of geriatric patients.…”
Section: Introductionmentioning
confidence: 99%